Understanding Distrust of the Public Sector Leading to Covid-19 Dissidence in Developing Nations - Zulmasyhur Zulmasyhur (Jurnal Studi Pemerintahan, 2022)
COVID-19 has drastic social, economic, and health impacts worldwide. However, mixed attitudes and behaviors of individuals towards Covid-19 ranging from the most responsible to the least bothering ones, have been evident over the last two years. Based on these mixed responses, the current study examines the impact of citizens' attitudes to self-isolation and distrust in official statistics on their threat perceptions and resultant COVID-19 dissidence. Quantitative research methodology with the survey technique was applied to collect data from 537 citizens of Jakarta, Indonesia. SmartPLS 3.0 software was used to assess the structural equation modeling and perform the regression analysis for examining the hypothesized relationships. The results revealed a significant impact of citizens' attitudes to self-isolation and distrust on official statistics in creating the COVID-19 dissidence. Likewise, the results showed the mediatory role of threat perceptions in transmitting the citizens' attitude and distrust in government in COVID-19 dissidence. Furthermore, the current study is a valuable addition to the existing body of literature by highlighting the factors that created the rebellious attitudes and behaviors among the citizens of Jakarta, Indonesia, during the crucial times of COVID-19.